Adaptive self-powered active vibration control to cable structures. (1st April 2023) - Li, Jin-Yang; Shen, Jiayang; Zhu, Songye
Abstract: High-performance vibration control is always preferred for cable structures that are inherently flexible and susceptible to dynamic excitations. Among different control categories, active control generally surpasses the other types of control (i.e., passive, semi-active, etc.) in terms of control performance. However, its large energy consumption and the potential instability concern hinder its wide-spread applications in relevant fields. In this regard, we propose a novel power-oriented adaptive self-powered active control system to address these concerns without compromising active control performance. In particular, this study explores the full potential of the newly proposed system analytically and numerically via a case study of a 135 m full-scale bridge cable. Moreover, its control performance is meticulously compared with that of an emerging passive controller, namely, an optimal inerter damper. Simulation results confirm that the proposed system successfully realized a considerably enhanced and broadband vibration mitigation performance than an optimal inerter damper without requiring an external energy supply. Slight modifications to the setup can further enable an easy transfer to other applications, shedding light on its promising future.